Methodology to compare front-end load and balance fees in pension funds - Chávez-Bedoya, Luis (Estudios de Economía, 2016)
In the present article we develop a discrete-time methodology to compare frontend load and balance fees in the accumulation phase of a defined-contribution pension fund under the system of individual accounts. Additionally, using various methods, we study the effect of considering risk and density of contributions in the performance and suitability of the aforementioned types of fees. Finally, we perform a practical application of the methodology to the Peruvian Private Pension System.